Asymptomatic perforated gastric duplication clogged by omentum, anorectal malformation and agenesis of the corpus callosum: A rare combination - Samia Belhassen; Salwa Ammar; Arije Zouaoui; Nouri Abdellatif (Wolters Kluwer Medknow Publications, 2019)
Gastric duplication cysts are uncommon congenital anomaly and its association with other malformations is rarely reported. Many theories exist for the development of these lesions. This case report describes coincidental detection of perforated gastric duplication clogged by the omentum associated with anorectal malformation and agenesis of the corpus callosum.